ANALISIS PERANCANGAN ARSITEKTUR ENTERPRISE DINAS PETERNAKAN MENGGUNAKAN TOGAF ADM 9.2 (STUDI KASUS: FUNGSI VAKSINASI HEWAN PADA DINAS PETERNAKAN BANDUNG BARAT) - prayoga, danar; Ramadhani, Luthfi; Praditya, Dhata (LPPM Institut Pendidikan Nusantara Global, 2023)
This study analyzes and plans an enterprise architecture for the animal vaccination function at the Department of Fisheries and Animal Husbandry of West Bandung Regency. Animal vaccination is a crucial step in maintaining health and protecting animal populations from diseases. The author employs the TOGAF ADM (The Open Group Architecture Framework - Architecture Development Method) approach to analyze the animal vaccination process and identify necessary improvements. The vaccination steps, workflow, and responsibilities of various stakeholders are evaluated using the TOGAF ADM. Stages such as defining business architecture, data, applications, and information technology are applied in this analysis. The current information technology infrastructure is also analyzed to identify the suitable needs of the enterprise architecture. The results are expected to provide recommendations for improving the animal vaccination process at the Department of Fisheries and Animal Husbandry of West Bandung Regency. With an enterprise architecture based on TOGAF ADM, it is anticipated that the efficiency of animal vaccination implementation can be enhanced. These recommendations can serve as a guide for similar institutions in optimizing the animal vaccination process. In other words, this research bridges the theory of enterprise architecture with practical applications in the context of animal vaccination, yielding potential solutions to enhance process efficiency and effectiveness.